Prehod iz vrtca v šolo na primeru izvedbe vzgojno-izobraževalnih dejavnosti zunaj prostora ustanove - Cencič, Majda (Revija za elementarno izobraževanje, 2021)
Implementation of educational activities outside the buildings of the institution has several advantages. For this reason, we were interested in the transition from preschool to the first grade of primary school in relation to the implementation of curricular activities in preschool or in the first grade of primary school outdoors. The results have shown that the external premises of the institution are statistically more frequently used by preschool teachers than by schoolteachers. Only in the implementation of the subject environment in the first grade compared to the implementation of curricular activities concerning society and nature in preschool outside the premises of the institution were no statistically significant differences detected.
Keywords: 1. razred; curricular activities; external space; first grade; kurikularne dejavnosti; prehod; preschool; school; school subjects; šola; transition; učni predmeti; vrtec; zunanji prostor